Stigma and family relationships of middle-aged gay men in recovery. Issue 1 (2nd January 2016) - del Pino, Homero E.; Moore, Mignon R.; Dacus, Jagadisa-devasri; McCuller, William J.; Fernández, Lawrence; Moore, Alison A.
ABSTRACT: The primary objective of this study was to explore how middle-aged gay men in recovery cope with stigma and family relationships. For gay men, perceptions of acceptance of their sexual orientation and degree of social connectedness can play a role in their recovery from alcohol and substance use disorders. Yet gay men may have a more difficult time accessing certain family-level health resources because their families of origin may stigmatize, reject, or silence them on account of their sexual orientation. Semi-structured interviews were used to explore how participants in recovery constructed and coped with their experiences of stigma, family relationships, and alcohol and substance use. Participants (30 gay men ages 50 to 64) completed a questionnaire and interview. We used constructivist grounded theory method and minority stress theory as a theoretical framework to interpret the data. We identified the following themes: Internalization of Stigma, Changes in Coping Strategies, and Ongoing Stigma. Future research should explore how to incorporate familial support into gay men's recovery, address ongoing internalized stigma, and develop a social response to stigma, rather than leaving it to individuals to confront on their own.